4(w-1)+w=8(w-1)+6

Simple and best practice solution for 4(w-1)+w=8(w-1)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(w-1)+w=8(w-1)+6 equation:



4(w-1)+w=8(w-1)+6
We move all terms to the left:
4(w-1)+w-(8(w-1)+6)=0
We add all the numbers together, and all the variables
w+4(w-1)-(8(w-1)+6)=0
We multiply parentheses
w+4w-(8(w-1)+6)-4=0
We calculate terms in parentheses: -(8(w-1)+6), so:
8(w-1)+6
We multiply parentheses
8w-8+6
We add all the numbers together, and all the variables
8w-2
Back to the equation:
-(8w-2)
We add all the numbers together, and all the variables
5w-(8w-2)-4=0
We get rid of parentheses
5w-8w+2-4=0
We add all the numbers together, and all the variables
-3w-2=0
We move all terms containing w to the left, all other terms to the right
-3w=2
w=2/-3
w=-2/3

See similar equations:

| 4k-26=10 | | .99+.89d=10+.89d | | F(a)=7/12-a | | 1(x-3)=5+2(2x-5)2123 | | x-(x/6)=4 | | 15z+15/5=15/5 | | -3a=2a+19 | | -26=-2(3x-8) | | 20+x=30-2x | | -5(p+1)=45 | | -3+10x=27+4x | | 3(x=4)+2=12 | | 15+4x-x=9x+9 | | -18=y+30-5y | | -9(x+1)=63 | | 23-11x=100 | | -15a=-6a-90 | | 5(n-5)+-3n=1 | | -6a-8=112 | | 5y(3)=32 | | 3+4x=2x-5 | | x+35=2x+15 | | 8(5+2x)=24 | | 2(7-6x)=-116 | | 195-3.75x=45 | | -10x=-6{4+3x} | | 4(0.5x-1)-4=2(x-1)-6 | | 120-45=15x | | 56-9p-11=-45 | | 272=-16t^2+96t+192 | | 2x+16=2/5x-5 | | 0.33x=x-6 |

Equations solver categories